Analysis of Diclofenac Sodium in Traditional Medicine (Jamu) for Rheumatism in Banjarmasin using TLC-UV-Vis Spectrophotometric Method - Syarbani, Syarbani; Lestari, Yulianita Pratiwi Indah; Hayati, Mardia (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Jamu is one of Indonesia's most consumed traditional medicines. The government has clearly stated that traditional medicines are strictly prohibited from containing chemicals, both isolated and synthetic. Diclofenac sodium is one of the Non-Steroid Anti Inflammation Drug (NSAID) class drugs that have an effect as a pain reliever and anti-inflammatory, which is also often misused in traditional medicine preparations. The purpose of this study is to determine whether there is a chemical content of diclofenac sodium contained in the preparation of jamu pegal linu circulating in Banjarmasin using thin-layer chromatography (TLC) and to determine whether the validation of the method using a UV-Vis spectrophotometer meets the established requirements. The results of qualitative analysis using thin-layer chromatography showed that 4 out of 7 samples identified positively contained diclofenac sodium with an Rf value of 0.825. The results of quantitative testing using a UV-Vis spectrophotometer showed the acquisition of an r-value of 0.9996, %RSD of 0.97%, % recovery of 95.28%, 92.82%, and 95.48% for the addition of standard solutions of 10 ppm, 15 ppm, and 20 ppm, as well as LOD & LOQ values of 1.1625 ppm and 3.8750 ppm. Based on the analysis results, it can be stated that 4 out of 7 samples of jamu pegal linu circulating in the Banjarmasin area are positive for diclofenac sodium with levels ranging from 10.257 - 18.465 mg/g (1.026% - 1.846%).